Historicity of Hadith Study and Its Learning Model in Islamic Universities in Indonesia and Uzbekistan (LPPM IAIN Kudus, 2025)
This research aims to explain the historicity of hadith study and its learning model in Indonesia and Uzbekistan by making the research locus of 3 (three) State Islamic Universities: State Islamic University (UIN) Sunan Kudus, UIN Syekh Wasil Kediri, and UIN Maulana Malik Ibrahim Malang as representations of Islamic universities in Indonesia and the Tashkent Islamic Institute as a representation of Islamic universities in Uzbekistan. This research used a qualitative approach with observation, interviews, and documentation as data collection techniques. The collected data were then analyzed descriptively and critically. The result shows that the network of scholars who entered Indonesia and Uzbekistan through trade routes intensified their struggles with hadith. The Prophet’s hadith is studied for its transmission, content, guidance, and application in these two countries. Hadith learning in universities, especially Islamic universities, is now a basic compulsory subject known as institute courses and is supported by facilities and infrastructure that enhance the comfort of the learning experience. Indonesia and Uzbekistan share concerns about studying the hadith of the Prophet PBUH because the hadith is the second source of Islamic law after the Qur’an. Hadith studies in Uzbekistan emphasize hadith studies of classic primary hadith books, while Indonesian hadith studies have been linked to global and contemporary issues.